Description System Communication Digital Learning in Schools Intermediate - Firdausi, Alfina Rizki; Hasanah, Rahma Uswatun; Anwaresha, Ummi Latifa (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
The rapid adoption of digital learning in Madrasah Tsanawiyah (MTs) demands a deep understanding of the effectiveness of the communication systems used. This Research is important because effective communication is the key to successful knowledge transfer in a digital environment, and often this process is hindered by noise and misinterpretation of messages. By analyzing the communication system through the lens of the Shannon-Weaver model, which focuses on the source, message, channel, and noise, we can specifically identify gaps and breakdowns in the exchange of information between teachers and students on digital platforms. This study aims to comprehensively describe the digital learning communication system in Mts, particularly in the context of the teacher's role as the source or transmitter and the students as the receivers or decoders of messages. The specific objective is to identify key elements of the channel system, encoding, decoding, and primary sources of noise, such as technical issues and information overload. This study uses a descriptive qualitative approach with a case study at one of the MtsN in Ponorogo. Data collection was carried out through in-depth interviews with teachers. The results show that the effectiveness of educational communication in digital learning at MTsN Ponorogo is highly determined by the quality of message encoding, as reflected in the choice of language and appropriate teaching methods. Field findings confirm that technical and semantic noise factors are the most significant variables hindering the knowledge transfer process.